Brivaracetam in the treatment of focal and idiopathic generalized epilepsies and of status epilepticus. Issue 5 (3rd May 2016) - Strzelczyk, Adam; Klein, Karl Martin; Willems, Laurent M.; Rosenow, Felix; Bauer, Sebastian
ABSTRACT: Brivaracetam is the latest approved antiepileptic drug in focal epilepsy and exhibits high affinity as SV2A-ligand. More than two thousand patients have received brivaracetam within randomized placebo-controlled trials. Significant median seizure reduction rates of 30.5% to 53.1% for 50 mg/d, 32.5% to 37.2% for 100 mg/d and 35.6% for 200 mg/d were reported. Likewise, 50% responder rates were 32.7% to 55.8% for 50 mg/d, 36% to 38.9% for 100 mg/d and 37.8% for 200 mg/d. Overall, brivaracetam is well tolerated. The main adverse events are fatigue, dizziness, and somnolence. Immediate switch from levetiracetam to brivaracetam at a conversion ratio between 10:1 to 15:1 is feasible, and might alleviate the behavioral side effects associated with levetiracetam. Brivaracetam has the potential to perform as an important, possibly broad-spectrum AED, initially in patients with drug-refractory epilepsies. Its intravenous formulation may be a new and desirable alternative for status epilepticus, but there is so far no experience in these patients.